The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1111/jsr.13656
|View full text |Cite
|
Sign up to set email alerts
|

Association of sleep duration and quality with immunological response after vaccination against severe acute respiratory syndrome coronavirus‐2 infection

Abstract: Summary Growing evidence suggests that sleep could affect the immunological response after vaccination. The aim of this prospective study was to investigate possible associations between regular sleep disruption and immunity response after vaccination against coronavirus disease 2019 (COVID‐19). In total, 592 healthcare workers, with no previous history of COVID‐19, from eight major Greek hospitals were enrolled in this study. All subjects underwent two Pfizer–BioNTech messenger ribonucleic acid (mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 44 publications
(73 reference statements)
2
14
0
1
Order By: Relevance
“…This large and representative example of HCWs represents a rather young and overall healthy population with only around 20% of participants reporting dissatisfaction with their sleep, while in the adult population dissatisfactory sleep is generally more common with more than 40% reporting some insomnia symptoms before the COVID-19 pandemic and more than 50% of the population during the pandemic in 2020 (Morin et al, 2021). The insomnia prevalence of 36% and the short sleep duration of only six hours in the first study investigating the association of sleep variables and the immunogenicity of COVID-19 vaccines might explain why the authors found a significant impact of the AIS and PSQI scores on antibody levels at some time points after adjustment for potential confounders (Athanasiou et al, 2023). It must be considered that both clinical scores include an item on sleep duration (Buysse et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This large and representative example of HCWs represents a rather young and overall healthy population with only around 20% of participants reporting dissatisfaction with their sleep, while in the adult population dissatisfactory sleep is generally more common with more than 40% reporting some insomnia symptoms before the COVID-19 pandemic and more than 50% of the population during the pandemic in 2020 (Morin et al, 2021). The insomnia prevalence of 36% and the short sleep duration of only six hours in the first study investigating the association of sleep variables and the immunogenicity of COVID-19 vaccines might explain why the authors found a significant impact of the AIS and PSQI scores on antibody levels at some time points after adjustment for potential confounders (Athanasiou et al, 2023). It must be considered that both clinical scores include an item on sleep duration (Buysse et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…Expert advice had been given that shift workers should avoid vaccinations on shift days and hospital inpatients should consider rescheduling their vaccinations due to the sleep disruptions associated with hospitalization (Zhu et al, 2021). However, the first and only previous study investigating the effects of sleep on antibody levels following COVID-19 vaccinations found no correlation between the duration of sleep two days prior and one day after the vaccination with antibody levels (Athanasiou et al, 2023). In light of this and our data, and because COVID-19 vaccinations represent an essential disease prevention measure (Benenson et al, 2021), COVID-19 vaccines should be applied in a timely manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While sarcoidosis may not, overall, increase the risk of adverse outcomes from respiratory infections, the burden of super-imposed infectious events may be higher for patients with sarcoidosis who often have reduced physiologic reserve and/or quality of life impairments. The results of recent research highlight the importance of sleep quantity in contributing to vaccine efficacy for the COVID-19 vaccine, with the evolving understanding that sleep acts as a ‘natural adjuvant’ to enhance short-term immune responses and long-term immune memory [45–48,49 ▪▪ ,50]. As patients with sarcoidosis have increased risk of impaired sleep [51,52] counselling patients on sleep practices during the pre and post vaccination weeks may be especially beneficial.…”
Section: Clinical Management: Minimizing the Burden Of Infections In ...mentioning
confidence: 99%